Sociological Debates on Gestational Surrogacy Between Legitimation and International Abolition - Bandelli, Daniela (Springer Nature, 2021)
This open access book discusses and analyses competing views and social implications of gestational surrogacy, which is making inroads as an option for parenthood as well as a work opportunity for women. It provides a rich account of transnational mobilizations for the abolition and regulation of surrogacy, with focus on United States, Italy and Mexico. The author critically assesses the core narratives of supporters and opponents of surrogacy, in order to understand this reproductive practice in light of some of the essential elements of contemporary societies, such as the "child at any cost" culture, individualism, technology and female emancipation. This book appeals to scholars, policy makers and all those who want to understand the controversial debate on this unprecedented method of family formation and life production.